Benchmark computations for 3D two-phase flows: A coupled lattice Boltzmann-level set study. (1st February 2017) - Safi, Mohammad Amin; Prasianakis, Nikolaos; Turek, Stefan
Abstract: Following our previous work on the application of the diffuse interface coupled lattice Boltzmann-level set (LB-LS) approach to benchmark computations for 2D rising bubble simulations, this paper investigates the performance of the coupled scheme in 3D two-phase flows. In particular, the use of different lattice stencils, e.g., D3Q15, D3Q19 and D3Q27 is studied and the results for 3D rising bubble simulations are compared with regard to isotropy and accuracy against those obtained by finite element and finite difference solutions of the Navier–Stokes equations. It is shown that the method can eventually recover the benchmark solutions, provided that the interface region is aptly refined by the underlying lattice. Following the benchmark simulations, the application of the method in solving other numerically subtle problems, e.g., binary droplet collision and droplet splashing on wet surface under high Re and We numbers is presented. Moreover, implementations on general purpose GPUs are pursued, where the computations are adaptively refined around the critical parts of the flow.